Microbial oxidation of medium chain fatty alcohol in the synthesis of sophorolipids by candida bombicola and its physicochemical characterization - Pulate, Vrushali Dengle; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2013)
Sophorolipids (SL) are glycolipid biosurfactants abundantly produced from different feedstocks by yeasts and have been widely developed for various applications. The amphipathic structures of sophorolipids imparts to them surfactant type properties. These biosurfactants are readily isolated in high yield and are nontoxic and biodegradable, which make them industrially interesting as surfactants or emulsifiers. Sophorolipid production was carried out using glucose as a hydrophilic source and lauryl alcohol C12-14, as a hydrophobic source by Candida bombicola (ATCC 22214). Process economics and environmental attractiveness was increased by using a low cost substrate. Optimization studies were carried out where the effect of glucose concentration, pH, temperature and metal ions on sophorolipid production was studied. Optimum production of sophorolipid obtained using lauryl alcohol (SLLA) was achieved after 96 h, the initial pH of the medium was 6.0 with 10 % glucose at 30 A degrees C. Primary characterization of SLLA was done by FTIR. The SLLA showed high physicochemical properties in terms of the surface activities when compared with synthetic surfactants including dodecyl tetraethylene glycol ether and sodium lauryl sulfate. The surface tension of SLLA thus obtained was found to be 24 mN/m with a critical micellar concentration (CMC) value of 0.68 mg/L. Antimicrobial testing showed that SLLA have potent antimicrobial activity against both gram negative bacteria, Escherichia coli (ATCC 8739) and gram positive cocci, Staphylococcus aureuss (ATCC 2079).
Keywords: Biosurfactants; Candida bombicola; CMC; Lauryl alcohol C12-14; sophorolipids; Surface tension